1940
DOI: 10.1017/s0022029900017696
|View full text |Cite
|
Sign up to set email alerts
|

Section D. The nutritional value of milk and milk products

Abstract: I. Introduction. II. General. III. Nutritional value as estimated in laboratory and field experiments. A. Raw milt (and butter in the cases of vitamins A and D). (o) General. (6) Vitamins. (i) General. (ii) Vitamin A and carotene. (iii) The vitamin B complex. (iv) Vitamin C. (v) Vitamin D. (c) Other factors. (i) Lactose. (ii) Soft curd milk. (iii) Minerals. (iv) Milk proteins. (v) Milk fat. B. Treated milk. (a) Heated milk. (i) General, (ii) Vitamins. (6) Irradiated and vitaminized milk. C. Milk products. (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1943
1943
1953
1953

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 191 publications
0
2
0
Order By: Relevance
“…Normally the fat-soluble pigment of the milk is preponderantly 0-carotene, and the ratio of 94% active carotene and 6% xanthophylls put forward by Gillam (1934) has been generally accepted. It has been known for some time, however, that the exact proportion may vary according to the composition of the earotenoids fed to the cow (Kon, 1940). The present results showed that 10-40 % of the total earotenoids secreted in cow milk fat were in the biologically inactive form (Table 2).…”
Section: Discussionmentioning
confidence: 41%
“…Normally the fat-soluble pigment of the milk is preponderantly 0-carotene, and the ratio of 94% active carotene and 6% xanthophylls put forward by Gillam (1934) has been generally accepted. It has been known for some time, however, that the exact proportion may vary according to the composition of the earotenoids fed to the cow (Kon, 1940). The present results showed that 10-40 % of the total earotenoids secreted in cow milk fat were in the biologically inactive form (Table 2).…”
Section: Discussionmentioning
confidence: 41%
“…This confirms the earlier findings of Cashell & Kon (cf. (212)) that in rats an exclusive diet of mineralized skim milk-leads to cataractous changes. When galactose diets were given to pregnant rats cataractous changes were observed in foetuses 16 days old (742); paralysis on galactose diets has also been reported (731,743).…”
Section: (Iii) Impurities In Casein Of Nutritional Significancementioning
confidence: 99%